2017
DOI: 10.12988/asb.2017.61143
|View full text |Cite
|
Sign up to set email alerts
|

NSGA-II for biological graph compression

Abstract: Examinations of a common biological reference organism, (E. coli), demonstrate that NSGA-II is able to provide a series of compressions at various ratios, allows a biologist to examine the organism's connective networks with a measure of certainty of connectiveness. This is due to a novel method of scoring the similarity of the compressed network to the origional during the graph's creation based on the number of false links added to the graph during the compression method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…There are multiple objectives: having sufficient levels of compression while also minimizing loss of information in the edges and their weights. Previous systems [23] of multiobjective compression examining the prevention of the development of fake edges using NSGA-II demonstrated that the tradeoff between compression and loss of detail using evolutionary methods is manageable even with high compression. Future work should examine this technique for weighted graphs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are multiple objectives: having sufficient levels of compression while also minimizing loss of information in the edges and their weights. Previous systems [23] of multiobjective compression examining the prevention of the development of fake edges using NSGA-II demonstrated that the tradeoff between compression and loss of detail using evolutionary methods is manageable even with high compression. Future work should examine this technique for weighted graphs.…”
Section: Discussionmentioning
confidence: 99%
“…There have also been examinations of multiple objective evolution being used to control the trade off between the compression ratio and the loss of detail [5], [23]. The use of these systems allows for the user of the system to have a high valued compression without the loss of informational data, which is a clear trade off in the compression.…”
Section: Related Workmentioning
confidence: 99%
“…The representation and methodology have evolved over the course of a number of previous studies (see, e.g. [9], [32], [16], [20]) and used successfully to address the compression of biological data. A brief description of the representation follows, and we refer the reader to these earlier studies for further details.…”
Section: A Compressionmentioning
confidence: 99%
“…Each chromosome in the population is a sequence of merges which must be local in that both nodes to be merged are within root 22 12 24 71 20 offset 21 94 12 19 7 merges, the first node is chosen randomly and its index is stored in the root. Next, a breadth-first search is performed from that node to find all other nodes within the specified distance; once these are found, one is chosen at random and the offset is set accordingly.…”
Section: B Initial Populationmentioning
confidence: 99%